KOMPONEN LAPORAN KEUANGAN PEMERINTAH DAERAH - Yalabi, Dian Apriani (LPPM Politeknik Saint Paul Sorong, 2021)
The components of local government financial statements discuss the elements or items that need to be informed in local government financial statements. Rules regarding the presentation of financial statement elements can also refer to government accounting standards that have been set. But that doesn't mean all posts have to have value. If a particular item does not have numbers, then it does not need to be forced to fill in its value and be presented in the financial statements. The purpose of this article is to provide an overview of the components of local government financial statements and present useful information for decision making and assessing accountability, financial performance of a reporting entity managed in making decisions both economic, social, and political decisions.